(untitled) (Revista de Artes Marciales Asiáticas, 2013)
Aim: Lower limb explosive strength and mae-geri kicking velocity are fundamental in karate competition; although it is unclear whether these variables could differentiate the high-level athletes. The objective of this research is to analyze the differences in the mae-geri kicking velocity and the counter-movement jump (CMJ) between a group of international top level karateka and another group of national-level karateka. Methods: Thirteen international-level karateka and eleven national-level karateka participated in the study. After a standard warm-up, CMJ height (in cm) and mae-geri kicking velocity (in m/s) was measured using an IR-platform and a high-speed camera, respectively. Results: Proceeding with MANCOVA to analyze the differences between groups controlling the effect of age, the results show that the international-level karateka demonstrated significantly higher levels of CMJ than national-level competitors (+22.1%, F = 9.47, p = 0.006, n2 = 0.311). There were no significant differences between groups in the mae-geri kicking velocity (+5,7%, F=0.80; p=0.38; n2=0.03). Conclusion: Our data shows, first, the importance of CMJ assessment as a tool to detect talent in karate and, second, that to achieve international-level in karate it may be important to increase CMJ levels to values similar to those offered here.